(3GdETQGa GdbVGFj Ydi GdJfajP GdLfGFj (B: s (3OQGSI ebGQfI (B/ s - (3QGej efUhQ YHGS GMeOs; (3YeQ eMeO SGde s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2014)
(3Ef JWhQ GdfXQI Edi GdLRGA GdYbGHj jYcS eOi GdJMhd aj GdacQ GdLfGFj(B: (3hGbJfGYg HaGYdjI GdYbhHGJ hGdJOGHjQ GdhbGFjI hbOQJgG Ydi ehGLgI BaI GdELQGe(B: (3Pdc Cf gPg GdXGgQI de JYQa JQGLYkG jPcQ HGdeDGRQI eY GdJhLg fMh GdJNaja ef MOI GdLRGA(B: (3aeSjQI GdGfMQGa JYQa JUGYOkG aj GdeLJeYGJ GdeJbOeI Ch GdeJCNQI efgG Ydi MO ShGA hgh eG jDOi Edi UYhHI GdeaGVdI Hjf GdCfXeI GdJj JYJeO Ydi GdUQGeI cCSGS YfO JbQjQ GdYbhHGJ hHjf GdCfXeI GdJj JJLg fMh GdHMK Yf HOGFd dgPg GdYbhHGJ (B. (3aGdLQjeI eQJHWI HGdeLJeY JJWhQ HJWhQg hJfeh Hfehg(B: (3hjQi GdHYV CfgG aj UGdM JbOe GdeLJeY(B: (3eeG jbdU GdQZHI aj GdbVGA YdjgG(B: (3Ke EfgG JNJda HGNJdGa GdYUhQ hGdXQha hGdOhds
(3GWQhMI (B((3eGLSJjQ(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdLfGFj, (B2014s
(3jTJed Ydj EQLGYGJ HdjhLQGajI(B: (3UaMI (B188-200s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdLfGFjs; (3GdLRGA GdYbGHis; (3GdeDGRQIs; (3GdeLJeYGJs; (3fXQjI GdETQGa Ydi GdJfajP GdYbGHj s; (3ETcGdGJ JfajP GdCMcGe GdYbGHjIs; (3fXGe GdbGVj GdeJNUU s; (3GdJfajP GdLfGFj s; (3GdeQGbHI GdEdcJQhfjI s; (3GdJfajP GdYbGHj s; (3GdeDSSI GdYbGHjI s; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdLfGFjs